SYNTHESIS, AND BIOLOGICAL ACTIVITIES OF SOME SCHIFF BASES DERIVATIVES - Mohammed, Raed; Ali, Hanan M. (Antis-Publisher, 2026)
Objective: This study aims to synthesize and evaluate the biological activities of four Schiff base compounds derived from the condensation of benzaldehyde and selected amine derivatives, with a focus on determining their anticancer, antibacterial, and antifungal potentials. Method: Four compounds—namely compound 1 [(E)-1-(4-chlorophenyl)-N-(6-methoxybenzo[d]thiazol-2-yl)methanimine], compound 2 [(E)-4-(((6-methoxybenzo[d]thiazol-2-yl)imino)methyl)phenol], compound 3 [(E)-5-((2-methylbenzylidene)amino)-2,3-dihydrophthalazine-1,4-dione], and compound 4 [(E)-5-((2-hydroxybenzylidene)amino)-2,3-dihydrophthalazine-1,4-dione]—were synthesized and subjected to in vitro screening. Results: Compound 1 exhibited the strongest anticancer activity, outperforming the other derivatives. Compounds 1 and 2 showed pronounced antibacterial effects against Staphylococcus aureus, while compound 4 demonstrated activity against Escherichia coli. Compounds 3 and 4 also displayed significant antifungal inhibition against Candida albicans. Novelty: The study identifies specific structure–activity relationships among newly synthesized Schiff bases, highlighting distinct bioactive profiles and offering promising lead compounds for future therapeutic development.